The Characteristic Features of the Academic Fiction Genre - Poghosyan, Syuzanna (Armenian Folia Anglistika, 2012)
The introduction of the English-American Academic Fiction Genre in the 20th and 21st centuries was a striking event in the world of literature. The genre was born in 1952 by two pieces of work published simultaneously – “The Groves of Academe” by Mary McCartney and “Lucky Jim” by K. Amis. Numerous talented authors followed the two ones, among them Malcolm Bradbury (1932-2000), Phillip Rote (1933), Alison Laurie (1926), John Maxwell Coetzee (1940) and Francine Prose (1947). The novels of this genre depict a whole chain of events where student-lecturer-family relationships are reflected. Academic Fiction Genre already has established and unique features. Each novel provides a detailed description of the academic setting where the main events unfold. Initially, light mockery was typical of this genre which, along with the gradual disappointment of the authors, developed into bitter and deep irony and later into tragedy. The climax of the novel is either a ball or an evening party where the main problems of the novel are highlighted and where the possible solutions to these problems are delicately mentioned. The present article discusses the introduction of the Academic Fiction Genre which has become one of the meaningful events in modern literature since it provides an opportunity to look at the inter-relations between an individual and the society and evaluate the genre peculiarities from a new perspective.